Nova classificação das vasculites pediátricas - Magalhães, Cláudia Saad [UNESP] (My University, 2011)
Vasculitis is an umbrella term for blood-vessel wall inflammation involving large, medium and small vessels, in different organs and systems. It encompasses several diseases with heterogeneous clinical features and similar inflammatory mechanisms. Several classification systems have been proposed, but those validated in adult cohorts did not result in similar sensitivity and specificity in children with the same disease. In order to review the new criteria development for paediatric vasculitis including Kawasaki disease, Henoch-Schönlein purpura, polyarteritis nodosa, Wegener granulomatosis, Takayasu arteritis, an outline of the validation steps of Eular-Printo-Pres criteria is presented. Internet based data collection from 1,398 paediatric cases in 97 centres and 36 countries was carried out. Physician diagnosis was the gold-standard and the nominal group technique was the process to reach consensus among specialists judging “difficult” cases. Proposed criteria resulted in sensitivity between 90% and 100% (power to “discriminate” patients with a single type of vasculitis) and specificity between 87% and 100% (the power to “exclude” cases with other diseases).

As vasculites, denominação genérica para inflamação da parede dos vasos sanguíneos, acometem vasos de diferentes calibres em diversos órgãos e tecidos e incluem doenças com manifestações clínicas heterogêneas e mecanismos inflamatórios semelhantes. Entre as diversas classificações propostas, as derivadas de coortes de adultos não têm a mesma sensibilidade e especificidade quando aplicadas em pacientes pediátricos com a mesma doença. Com o objetivo de revisar o processo de desenvolvimento dos novos critérios propostos para a doença de Kawasaki, púrpura de Henoch-Schönlein, poliarterite nodosa, granulomatose de Wegener e arterite de Takayasu, um sumário do processo de validação dos critérios Eular-Printo-Pres é apresentado. Os dados clínicos de 1.398 crianças e adolescentes com vasculites, provenientes de 97 serviços em 36 países, foram coletados por meio da Internet. O diagnóstico feito pelo médico foi o padrão ouro e o consenso nominal entre especialistas, o processo para resolução de “casos difíceis”. Os critérios propostos resultaram em sensibilidade entre 90% e 100% (capacidade de “discriminar” pacientes com determinado tipo de vasculite) e especificidade entre 87% e 100% (capacidade de “excluir” uma proporção de casos com outras doenças).
The new classification of pediatric vasculitis
Keywords: Kawasaki disease; Henoch-Schönlein purpura; Polyarteritis nodosa; Takayasu arteritis; Vasculitis; Wegener granulomatosis; Arterite de Takayasu; Doença de Kawasaki; Granulomatose de Wegener; Púrpura de Henoch-Schönlein; Poliarterite nodosa; Vasculites